Evaluating 'Power 4 a Healthy Pregnancy' (P4HP) - protocol for a cluster randomized controlled trial and process evaluation to empower pregnant women towards improved diet quality - R. M. Renske van Lonkhuijzen; S. Susanne Cremers; J. H. M. Jeanne de Vries; E. J. M. Edith Feskens; M. A. E. Annemarie Wagemakers (BMC, 2022)
Abstract Background In general during pregnancy, women are aware of the importance of good diet quality, interested in nutrition, and receptive to changing dietary intake. However, adherence to dietary guidelines is sub-optimal. A pregnant woman's first information source regarding nutrition information is her midwife. Healthy nutrition promotion by midwives may therefore be very promising, but midwives face multiple barriers in providing nutritional support. Empowering pregnant women to improve their diet quality is expected to improve their health. Therefore an empowerment intervention has been developed to improve diet quality among pregnant women. The objective of this study is to evaluate the effectiveness and feasibility of Power 4 a Healthy Pregnancy (P4HP). P4HP aims to empower pregnant women to have a healthier diet quality. Methods/design This study applies a mixed methodology consisting of a non-blinded cluster randomized trial with an intervention (P4HP) group and a control group and a process evaluation. Midwifery practices, the clusters, will be randomly allocated to the intervention arm (n = 7) and control arm (n = 7). Participating women are placed in intervention or control conditions based on their midwifery practice. Each midwifery practice includes 25 pregnant women, making 350 participants in total. Health related outcomes, diet quality, empowerment, Sense of Coherence, Quality of Life, and Self-Rated Health of participants will be assessed before (T0) and after (T1) the intervention. The process evaluation focuses on multidisciplinary collaboration, facilitators, and barriers, and consists of in-depth interviews with midwives, dieticians and pregnant women. Discussion This study is the first to evaluate an empowerment intervention to improve diet quality in this target population. This mixed method evaluation will contribute to knowledge about the effectiveness and feasibility regarding diet quality, empowerment, health-related outcomes, multidisciplinary collaboration, facilitators and barriers of the empowerment intervention P4HP. Results will help inform how to empower pregnant women to achieve improved diet quality by midwives and dieticians. If proven effective, P4HP has the potential to be implemented nationally and scaled up to a long-term trajectory from preconception to the postnatal phase. Trial registration The trial is prospectively registered at the Netherlands Trial Register ( NL9551 ). Date registered: 19/05/2021.